Interleukin-18 levels and mouse Leydig cell apoptosis during lipopolysaccharide-induced acute inflammatory conditions. (September 2020) - Inoue, Taketo; Aoyama-Ishikawa, Michiko; Uemura, Mikiko; Yamashita, Hayato; Koga, Yuka; Terashima, Mariko; Usami, Makoto; Kotani, Joji; Hirata, Junichi
Highlights: IL-18 is an indispensable cytokine in the maintenance of homeostasis in the testis. LPS increases TNF-α and IL-6 levels but not IL-18 levels in Leydig cells. IL-18 levels are significantly increased in macrophages after LPS stimulation. High-dose IL-18 induces Leydig cell apoptosis via a death-receptor-mediated pathway. The overproduction of IL-18 is harmful to Leydig cells during acute inflammation. Abstract: Interleukin (IL)-18 is an inflammasome-mediated cytokine produced by germ cells, Leydig cells, and resident macrophages that is indispensable in the maintenance of homeostasis in the testis. We previously demonstrated that endogenous IL-18 induces testicular germ cell apoptosis during acute inflammation when plasma IL-18 levels are very high. However, the impact of acute inflammation and IL-18 on Leydig cells remained unclear. TM3 cells, a mouse Leydig cell line, and RAW264.7 cells, a mouse macrophage cell line, were stimulated with lipopolysaccharide (LPS) or recombinant IL-18 (rIL-18). We assessed the expression of inflammatory cytokines, caspase cleavage, and markers of apoptotic pathways. In Leydig cells, caspase 3 cleavage was increased and death-receptor-mediated apoptotic pathways were activated after LPS stimulation. However, LPS stimulation did not increase IL-18 expression in the Leydig cell line. When high-dose rIL-18 was administered to the Leydig cell line to mimic levels seem after inflammation, rIL-18 upregulated Tnf-α mRNA, Fadd mRNA, and Fas protein, promoted cleavage of caspase-8 and caspase-3, and induced apoptosis. Low-dose rIL-18 did not stimulate apoptosis. To determine if the high level of IL-18 seen in the testes after inflammation was derived from immune cells, we examined IL-18 protein expression in a macrophage cell line, RAW264.7. In contrast to the TM3 cells, IL-18 was significantly increased in RAW264.7 cells after LPS stimulation. These results suggest that high-dose IL-18 derived from macrophages is harmful to Leydig cells. Reducing the overexpression of IL-18 could be a new therapeutic approach to prevent Leydig cell apoptosis as a result of acute inflammation.